A social assessment of urban parkland: Analyzing park use and meaning to inform management and resilience planning. Issue 62 (August 2016) - Campbell, Lindsay K.; Svendsen, Erika S.; Sonti, Nancy F.; Johnson, Michelle L.
Highlights: Park use and social meaning can be assessed via a mixed-method approach. Parks enable recreation, interaction with nature, social ties, and place attachment. Urban parks function as social resources and produce cultural ecosystem services. A replicable method enables assessment of changes in cultural ecosystem services. Social assessment can inform multi-scalar park management and resilience planning. Abstract: Globally, municipalities are tackling climate adaptation and resilience planning. Urban green space has crucial biophysical buffering capacities, but also affects social interactions and human well-being. This paper considers the social dimension of urban green space, through an assessment focused on park use, function, and meanings, and compares results to categories of cultural ecosystem services. We develop a mixed-method approach for assessment of uses and social meanings of parkland and pilot this method in 2140 acres of parkland in waterfront neighborhoods surrounding New York City's Jamaica Bay, an area heavily affected by Hurricane Sandy. This method combines observation of human activities and signs of prior human use with structured interviews of park users. We find that urban parkland is a crucial form of 'nearby nature' that provides space for recreation, activities, socialization, and environmental engagement and supports place attachment and social ties. We show that parks, through their use by and interactions with humans, are producing vital cultural ecosystem services that may help to strengthen social resilience. Certain services were more easily detectable than others via our assessment technique, including recreation, social relations, and sense of place. The assessment method was designed to be spatially explicit, scalable, and replicable; natural resource managers engaged in park management and/or resilience planning could apply this method across individual sites, in particular districts—such as vulnerable waterfront areas, and citywide. This study demonstrates a way in which cultural ecosystem services and an understanding of social meaning could be incorporated into park management and resilience planning.